Economic empowerment through rural tourism: the case of Tarapith – a religious tourism destination in Birbhum District of West Bengal, India - Suman Kumar Kundu, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
In developing countries like India rural tourism can be harnessed as a strategy for upgrading the quality of life of the rural poor . Although India is rich with potential tourism destinations distributed over remote corners of the country, due priority has not been given to strengthening the tourism infrastructure of these destinations so that they can attract domestic as well as international tourists. Yet, if properly managed, rural tourism can reduce the existing backwardness of the rural community by diversifying employment opportunities based on local tourism assets. In the present study of Tarapith – a religious tourism destination of the Birbhum district in West Bengal, an attempt was made to show the nature of economic empowerment that may be created through rural tourism. It was found that a significant impact of rural tourism upon local community was perceived by the local people.